Case Report: Non-traumatic Unilateral Forelimb Arterial Thrombosis Associated With Hyperadrenocorticism in a Dog - Eom, Tae-Yoon; Choi, Ju-Won; Yoon, Kyong-Ah; Jeong, Soon-Wuk; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2021)
A 16-year-old spayed female Pomeranian dog was presented to the hospital with an acute onset of pain and non-weight-bearing lameness in the right forelimb. On physical examination, knuckling, coolness, pain, and cyanosis were observed in the affected forelimb. Peripheral blood glucose concentration and body surface temperature differed between the right and left forelimbs. Hypercoagulable thromboelastographic results and increased D-dimer levels were suggestive of thrombus. Accordingly, recombinant tissue plasminogen activator (rtPA) was administered intravenously. Prompt clinical improvements (including restored warmth of the affected limb) occurred, and rtPA was discontinued after two shots administered 2 h apart owing to concerns of bleeding side effects. The dog was discharged 6 days after admission, and outpatient treatment with clopidogrel was continued for the prevention of re-thrombosis. Following patient stabilization, further examinations for underlying diseases of hypercoagulability were conducted; hyperadrenocorticism (HAC) was diagnosed, and oral trilostane therapy was thus administered. Eight weeks later, the patient regained normal mobility. Finally, in the present canine patient with arterial thrombosis, thrombolysis with rtPA successfully improved clinical symptoms and the following administration of clopidogrel inhibited the formation of additional thrombus.